2020
DOI: 10.1038/s41379-020-0605-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection and assessment of capsular invasion, vascular invasion and lymph node metastasis volume in thyroid carcinoma using microCT scanning of paraffin tissue blocks (3D whole block imaging): a proof of concept

Abstract: In the modern era, detailed pathologic characteristics of a thyroid tumor are crucial to achieve accurate diagnosis and guide treatment. The presence of capsular invasion (CI) is diagnostic for carcinoma, whereas vascular invasion (VI) and nodal metastasis (NM) are included in risk stratification. However, the very definition of CI and VI is surrounded by controversies and an accurate assessment of NM is lacking. Whole Block Imaging (WBI) by microCT is a new imaging modality to create 3D reconstruction of whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…However, combining WSI and micro-CT image has great potential to improve the histopathologic diagnosis because 3D morphologic structure can be also evaluated easily without additional resection and tissue exhaustion. Xu et al 13 mentioned that micro-CT image can detect additional foci of capsular invasion of thyroid carcinoma missed by the initial H&E slide, and volume of nodal metastasis measured on micro-CT image was most accurate compared with the conventional two-dimensional measurement on WSI. In addition, they suggested that among other things, micro-CT has the potential to increase the detection rate of capsular invasion and better define criteria for capsular invasion and vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, combining WSI and micro-CT image has great potential to improve the histopathologic diagnosis because 3D morphologic structure can be also evaluated easily without additional resection and tissue exhaustion. Xu et al 13 mentioned that micro-CT image can detect additional foci of capsular invasion of thyroid carcinoma missed by the initial H&E slide, and volume of nodal metastasis measured on micro-CT image was most accurate compared with the conventional two-dimensional measurement on WSI. In addition, they suggested that among other things, micro-CT has the potential to increase the detection rate of capsular invasion and better define criteria for capsular invasion and vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of interstitial pneumonia, Ketsamenis et al 8 demonstrated that the small airways, blood vessels, and alveoli of the lungs could be clearly visualized on micro-CT. Albers et al 10 scanned murine lung samples with free-propagation phase-contrast micro-CT and reported that micro-CT has the potential to improve workflow aspects of histologic analysis, such as determination of the cutting position. Xu et al 13 assessed thyroid carcinoma using micro-CT images of paraffin tissue blocks. According to their report, capsular invasion and vascular invasion could be detected and volume of nodal metastasis could be assessed by micro-CT images, even if the images were not present on serially sectioned hematoxylin and eosin (H&E)estained slides.…”
mentioning
confidence: 99%
“…MicroCT imaging of whole blocks of tissue embedded in paraffin or polymers is a new imaging modality to create 3D reconstruction of whole tissue block with microscopic level resolution 16,17 . The method has been used on invaded lymph nodes, placental villi, nerves, bones, lung and is promised to new developments 18–21 . The detection of wear particles from implanted biomaterials has been a problem in orthopaedic surgery for decades.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, new imaging modalities have emerged in the field of diagnostic pathology. Multiple large-scale studies have shown that whole slide images (WSI) have similar imaging efficiency as conventional microscopic examination of H and E glass slides [4]. However, conventional glass slides and WSIs provide information on only two dimensions of a tumor, which is in fact a three-dimensional entity.…”
Section: Introductionmentioning
confidence: 99%